Preparedness for a 'no-notice' mass-casualty incident: a nuclear detonation scenario. (4th May 2022) - Coleman, C. Norman; Cliffer, Kenneth D.; DiCarlo, Andrea L.; Homer, Mary J.; Moyer, Brian R.; Loelius, Shannon G.; Tewell, Adam W.; Bader, Judith L.; Koerner, John F.
Abstract: Purpose: An effective response for a mass-casualty incident requires understanding the relevant basic science and physical impact; detailed preparedness among jurisdictions; and clear, sequential response planning, including formal operational exercises, logistics, interagency, and public-private coordination, rapid activation of resilience, and continual improvement from lessons learned and new knowledge. This ConRad 2021 meeting report describes steps for civilian medical and public health response planning for a nuclear detonation; the utility of this type of planning for broader application; and extension of this planning to the international community. Conclusion: A nuclear detonation requires a response within minutes to what will be a large-scale disaster complicated by radiation, including some elements that are similar to a broad range of incidents. The response could be further complicated if multiple incidents occur simultaneously. Required are detailed planning, preparedness and scripting for an immediate operational response, addressing clinical manifestations of evolving radiation illness, and flexibility to adapt to a rapidly changing situation. This need translates into the use of just-in-time information; effective, credible communication; situational awareness on a global scale; and a template upon which to apply capabilities in a multi-sector response. This effort is greatly facilitated using a 'playbook' approach, the basics of which are presented.